Advancement of Optical Methods in Experimental Mechanics, Volume 3 Proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics (Conference Proceedings of the Society for Experimental Mechanics Series,, 2018)
Advancement of Optical Methods in Experimental Mechanics, Volume 3 of the Proceedings of the 2017 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the third volume of nine from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of optical methods ranging from traditional photoelasticity and interferometry to more recent DIC and DVC techniques, and includes papers in the following general technical research areas.